2022
DOI: 10.1556/2006.2022.00053
|View full text |Cite
|
Sign up to set email alerts
|

Gaming motivations and gaming disorder symptoms: A systematic review and meta-analysis

Abstract: Background and aims The present systematic review and meta-analysis aimed to synthesize the available literature on the relationship between gaming motivations and gaming disorder symptoms. Specifically, to (1) explore what gaming motivation questionnaires and classifications are used in studies on gaming disorder symptoms and (2) investigate the relationship between motivational factors and symptoms of gaming disorder. Method An electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 145 publications
2
23
0
Order By: Relevance
“…This general parallelism could indicate that fantasy and coping/escape motives can have a similar negative function. At the other end, recreation motives are least strongly related with video gaming problems, replicating previous results (Bäcklund et al, 2022; Kircaburun et al, 2020; Moudiab & Spada, 2019). Again, this converges with evidence from other behavioral domains in which fun, thrill, or entertainment motives are unrelated to problems derived from those activities, or even protect against them (see Barrada et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…This general parallelism could indicate that fantasy and coping/escape motives can have a similar negative function. At the other end, recreation motives are least strongly related with video gaming problems, replicating previous results (Bäcklund et al, 2022; Kircaburun et al, 2020; Moudiab & Spada, 2019). Again, this converges with evidence from other behavioral domains in which fun, thrill, or entertainment motives are unrelated to problems derived from those activities, or even protect against them (see Barrada et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, both the mental health of children and their parents are related to GD ( 33 ). Symptoms of GD are linked to motivations such as the avoidance of negative emotions, escapism, stress relief, and in-game social interactions ( 34 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…The motives for gaming have been identified as important predictors of GD. Studies have shown that the use of gaming as an escape from normal lives and gaming as a way of coping in particular are related to more problematic gaming behavior ( 22 ).…”
Section: Introductionmentioning
confidence: 99%